2024
DOI: 10.7759/cureus.62443
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Considerations in the Use of Artificial Intelligence and Machine Learning in Health Care: A Comprehensive Review

Mitul Harishbhai Tilala,
Pradeep Kumar Chenchala,
Ashok Choppadandi
et al.

Abstract: Artificial intelligence (AI) and machine learning (ML) technologies are revolutionizing health care by offering unprecedented opportunities to enhance patient care, optimize clinical workflows, and advance medical research. However, the integration of AI and ML into healthcare systems raises significant ethical considerations that must be carefully addressed to ensure responsible and equitable deployment. This comprehensive review explored the multifaceted ethical considerations surrounding the use of AI and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…In another study conducted by Harishbhai Tilala et al it is concluded that by addressing issues such as data privacy and security, algorithmic bias, transparency, clinical validation, and professional responsibility, healthcare stakeholders can navigate the ethical complexities surrounding AI and ML integration in health care while safeguarding patient welfare and upholding the principles of beneficence, non-maleficence, autonomy, and justice. By embracing ethical best practices and fostering collaboration across interdisciplinary teams, the healthcare community can harness the full potential of AI and ML technologies to usher in a new era of personalized data-driven healthcare that prioritizes patient well-being and equity [58]. There are other challenges and limitations in implementing AI in the current healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted by Harishbhai Tilala et al it is concluded that by addressing issues such as data privacy and security, algorithmic bias, transparency, clinical validation, and professional responsibility, healthcare stakeholders can navigate the ethical complexities surrounding AI and ML integration in health care while safeguarding patient welfare and upholding the principles of beneficence, non-maleficence, autonomy, and justice. By embracing ethical best practices and fostering collaboration across interdisciplinary teams, the healthcare community can harness the full potential of AI and ML technologies to usher in a new era of personalized data-driven healthcare that prioritizes patient well-being and equity [58]. There are other challenges and limitations in implementing AI in the current healthcare system.…”
Section: Discussionmentioning
confidence: 99%